Cancer-Preventive Role of Bone Marrow-Derived Mesenchymal Stem Cells on Colitis-Associated Colorectal Cancer: Roles of Gut Microbiota Involved - He, Ruohang; Han, Chaoqun; Li, Ying; Qian, Wei; Hou, Xiaohua (Frontiers in Cell and Developmental Biology, 2021)
Background: Mesenchymal stem cells (MSCs) are widely studied in inflammatory bowel disease (IBD) in preclinical rodent model and clinical patients. However, previous studies have produced controversial results regarding whether MSCs promote or inhibit tumor development. This study aims to evaluate the role of bone marrow-derived MSCs and the potential mechanism in colitis-associated colon cancer model (CAC). Methods: MSCs were isolated from bone marrow of GFP-transgenic mice and identified by flow cytometry. CAC mice model was induced by azoxymethane (AOM) and dextran sulfate sodium (DSS) and MSCs were injected intraperitoneally (i.p.) once per week. Weight loss, colon length, tumor number and average tumor size were assessed macroscopically. MSCs localization was detected by immunofluorescence staining, tumor cell proliferation and apoptosis were measured by immunohistochemistry staining of Ki-67 and TUNEL assay, respectively. The colonic tumor tissues were isolated for RNA-seq and fecal samples were collected for 16s rRNA sequencing of microbiome. Results: After injection intraperitoneally, MSCs could migrate to colon and suppress initiation of colitis-related neoplasm. This tumor suppressive effect was characterized by less weight loss, longer colon length and decreased tumor numbers. Moreover, MSCs decreased tumor cell proliferation and increased tumor cell apoptosis. Furthermore, MSCs could inhibit chronic inflammation assessed by RNA-sequencing and promote gut microbiome normalization detected by 16S rRNA sequencing. Conclusion: The results proven that MSCs could migrate to colon, inhibit chronic inflammation and regulate gut microbiome dysbiosis so as to suppress the development of CAC.